Pulmonary embolectomy – where in the aspect of the new European Society of Cardiology guidelines for diagnosis and management of acute pulmonary embolism of 2009 is a place for cardiac surgery? Case report - Rachwalik, Maciej; Bielicki, Grzegorz; Dumański, Andrzej; Kustrzycki, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
The case of a 53-year-old female patient with multiple injuries in the area of the pelvis and the chest due to communicational trauma is described. Diagnosis revealed fracture of two femoral bones, pubic and sacral bone fracture with displacement of bone fragments, collar bone fracture, as well as fracture of ribs 2, 3 and 4. Extended diagnosis also showed pneumothorax, which was supplied by suction drainage. On the third day of hospitalization increasing respiratory insufficiency appeared. In additional examination (CT with contrast) pulmonary embolism was revealed. The patient was transported to a cardio-surgical clinic, where the operation of removing the embolism was performed. A quick decision to change the treatment profile from injury-orthopedic status to cardiological-cardio-surgical status allowed us to control the severe emergency status of the patient, which in 7-11% of cases is terminal.